The Effect of Communication Media, Socialization Methods, and Community Participation on Community Resilience Mediated by Disaster Preparedness Behavior in the Empowerment Program of BPBD Bandar Lampung City - Nindi Aulia; Febrianty; Ayu Nursari (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of communication media, socialization methods, and community participation on community resilience through disaster preparedness behavior in the empowerment program of the Regional Disaster Management Agency (BPBD) of Bandar Lampung City. The phenomenon of increasing disaster intensity and community vulnerability requires an effective empowerment strategy, particularly in building community preparedness and resilience. This study uses a quantitative approach with a survey method of the community involved in the BPBD program. Path analysis is used to determine the direct and indirect relationships between variables. The results show that communication media and socialization methods have a significant effect on disaster preparedness behavior. In addition, community participation has been shown to strengthen community resilience both directly and through increased preparedness behavior. These findings confirm that optimizing communication media, implementing appropriate socialization methods, and increasing community involvement have a strategic role in building a resilient community against disasters. This study has practical implications for BPBD in designing empowerment programs that are more adaptive, participatory, and effective in increasing community resilience.